Characterization of pertussis-like toxin from Salmonella spp. that catalyzes ADP-ribosylation of G proteins - Tamamura, Yukino (Sci Rep, 2017)
Salmonella Typhimurium definitive phage type (DT) 104 produces a pertussis-like toxin (ArtAB-DT104), which catalyzes ADP-ribosylation of pertussis toxin sensitive G proteins. However, the prevalence of ArtAB and its toxicity have not been established. We report here that, in addition to DT104, S. Worthington, and S. bongori, produce ArtAB homologs, designated ArtAB-SW and ArtAB-Sb, respectively. We purified and characterized these ArtAB toxins, which comprise a 27-kDa A subunit (ArtA) and 13.8-kDa pentameric B subunits (ArtB). While the sequence of the A subunit, which is ADP-ribosyltransferase, is similar to the A subunit sequences of other ArtABs, the B subunit of ArtAB-Sb is divergent compared to the B subunit sequences of other ArtABs. Intraperitoneal injection of purified ArtABs was fatal in mice; the 50% lethal doses of ArtAB-DT104 and ArtAB-SW were lower than that of ArtAB-Sb, suggesting that ArtB plays an influential role in the toxicity of ArtABs. ArtABs catalyzed ADP-ribosylation of G proteins in RAW 264.7 murine macrophage-like cells, and increased intracellular cyclic AMP levels. ArtAB-DT104 and ArtAB-SW, but not ArtAB-Sb, stimulated insulin secretion in mice; however, unlike Ptx, ArtABs did not induce leukocytosis. This disparity in biological activity may be explained by differences in ADP-ribosylation of target G proteins.